The relationship between innovation & dynamic capability : Malaysia perception/view - Wong, Wei Jin (2017)
Purpose – The purpose of this paper is to provide better insights into the relationship between dynamic capabilities and innovation. It links dynamic capability with innovation and indicates the ways they can be related.